2023
DOI: 10.1161/cir.0000000000001128
|View full text |Cite|
|
Sign up to set email alerts
|

KIDS SAVE LIVES: Basic Life Support Education for Schoolchildren: A Narrative Review and Scientific Statement From the International Liaison Committee on Resuscitation

Abstract: BACKGROUND: Basic life support education for schoolchildren has become a key initiative to increase bystander cardiopulmonary resuscitation rates. Our objective was to review the existing literature on teaching schoolchildren basic life support to identify the best practices to provide basic life support training in schoolchildren. METHODS: After topics and subgroups were defined, a comprehensive literature search was conducted. Systematic reviews and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 142 publications
0
32
0
1
Order By: Relevance
“…However, it could be demonstrated that schoolchildren from the age of 4 to 7 years can adequately make an emergency call [33–35] or follow the instructions of an automatic external defibrillator [36,37]. In addition to that, several authors describe that a playful approach in terms of CPR at early ages promotes motivation and interest in schoolchildren under 12 years [5 ▪▪ ,33–37]. Comprehensibly, annual repetition leads to a consolidation of practical CPR-skills, which sustainably increases the willingness and self-confidence related to the initialization of resuscitation measures in later years [38–40].…”
Section: Starting Agementioning
confidence: 99%
See 4 more Smart Citations
“…However, it could be demonstrated that schoolchildren from the age of 4 to 7 years can adequately make an emergency call [33–35] or follow the instructions of an automatic external defibrillator [36,37]. In addition to that, several authors describe that a playful approach in terms of CPR at early ages promotes motivation and interest in schoolchildren under 12 years [5 ▪▪ ,33–37]. Comprehensibly, annual repetition leads to a consolidation of practical CPR-skills, which sustainably increases the willingness and self-confidence related to the initialization of resuscitation measures in later years [38–40].…”
Section: Starting Agementioning
confidence: 99%
“…Comprehensibly, annual repetition leads to a consolidation of practical CPR-skills, which sustainably increases the willingness and self-confidence related to the initialization of resuscitation measures in later years [38–40]. Therefore, expert associations recommend starting CPR training under the age of 12 years [5 ▪▪ ].…”
Section: Starting Agementioning
confidence: 99%
See 3 more Smart Citations